2020
DOI: 10.1021/acs.joc.0c00754
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Optical Properties of Di-m-benzihexaphyrins (1.1.0.0.0.0) and Di-m-benziheptaphyrins (1.0.1.0.0.0.0): Blackening of m-Phenylene-Linked Dicarbaporphyrinoids by Simple π-Expansion

Abstract: Acid-catalyzed condensation of a newly prepared di-m-benzipentapyrrane with appropriate mono- and diheterocyclic dialcohols selectively produced stable di-m-benzihexaphyrins and di-m-benziheptaphyrins with only two meso-carbon bridges. Single-crystal X-ray diffraction analyses reveal planar conformation with slight distortion of bridged phenylene rings. Despite the presence of m-phenylene units interrupting the global delocalization, the presence of bithiophene units in di-m-benziheptaphyrins 3a–b exhibits alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Carbazole-containing expanded porphyrins may be viewed as being a class of expanded carbaporphyrins, 21,22 systems with one or more carbon donors incorporated into the central core. [23][24][25][26][27][28][29] These unique macrocycles exhibit a diverse range of properties, including unusual aromaticity and chirality features, [30][31][32] as well as serving as potential ligands. [33][34][35][36] Among the various expanded carbaporphyrinoids reported to date, those with two embedded polyaromatic hydrocarbons or related heterocycles (PAHs) are still relatively rare and their metalation chemistry has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Carbazole-containing expanded porphyrins may be viewed as being a class of expanded carbaporphyrins, 21,22 systems with one or more carbon donors incorporated into the central core. [23][24][25][26][27][28][29] These unique macrocycles exhibit a diverse range of properties, including unusual aromaticity and chirality features, [30][31][32] as well as serving as potential ligands. [33][34][35][36] Among the various expanded carbaporphyrinoids reported to date, those with two embedded polyaromatic hydrocarbons or related heterocycles (PAHs) are still relatively rare and their metalation chemistry has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Lash's group [8,15,28] and Latos‐Grażyński's group [10,19,20,27,29–31] and others [20,21,23,32–35] have extensively investigated the phenylene containing porphyrinoids, discussed their aromatic characteristics and shown their ability to form organometallic complexes by involving phenylene “C” along with pyrrole “N”s in coordination. Although the aromatic nature of m / p ‐phenylene containing porphyrins have been studied to greater extent but the aromaticity was not investigated thoroughly with m / p ‐phenylene containing expanded porphyrinoids since the reports on m / p ‐phenylene containing expanded porphyrins are relatively very few [20,33,36–39] . We recently reported the synthesis of [24π] dithia meta ‐benzisapphyrins 1 and [22π] dithia para ‐benzisapphyrins 2 and showed that the dithia p ‐benzisapphyrins 2 were aromatic whereas the dithia m ‐benzisapphyrins 1 were nonaromatic in nature [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the aromatic nature of m/p-phenylene containing porphyrins have been studied to greater extent but the aromaticity was not investigated thoroughly with m/pphenylene containing expanded porphyrinoids since the reports on m/p-phenylene containing expanded porphyrins are relatively very few. [20,33,[36][37][38][39] We recently reported the synthesis of [24π] dithia meta-benzisapphyrins 1 and [22π] dithia parabenzisapphyrins 2 and showed that the dithia p-benzisapphyrins 2 were aromatic whereas the dithia m-benzisapphyrins 1 were nonaromatic in nature. [33] In continuation of our efforts in synthesizing more examples of expanded m/p-benziporphyrinoids to understand their structure, spectral and aromatic properties, herein we report our successful synthesis of nonaromatic [32π] m-benziheptaphyrins 3 a/3 b and aromatic [30π] p-benziheptaphyrins 4 a/4 b by adopting [5 + 2] condensation strategy using readily synthesized precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Such aromaticity with strong characteristic absorption often displays unique features with multifaceted optical applications. Incorporation of phenylene rings into the porphyrin core provide unique strategy toward carbaporphyrinoids with varied aromatic properties . For instance, an unsubstituted m -benziporphyrin exhibits nonaromaticity, whereas the p -benziporphyrins shows switchable aromatic features . On the contrary, a subtle difference in the aromaticity is realized in di- p -benziporphyrin A with a “figure-eight” structure induced by its conformational change when two phenylene rings are incorporated onto the porphyrin core (Figure ).…”
mentioning
confidence: 99%